Bilateral Wilms Tumor with TP53-Related Anaplasia. (May 2013) - Popov, Sergey D.; Vujanic, Gordan M.; Sebire, Neil J.; Chagtai, Tasnim; Williams, Richard; Vaidya, Sucheta; Pritchard-Jones, Kathy
Wilms tumor (WT) with diffuse anaplasia has an unfavorable prognosis and is often (>70%) associated with mutations in the TP53 gene. Although most WTs are unilateral, 5–10% are bilateral, and they are almost always present with nephrogenic rests. The latter are considered a precursor of WT. Two cases of bilateral WTs with nephroblastomatosis, in which anaplastic changes were detected over a period of time, were analyzed using clinical, radiological, histopathological, and molecular-genetic data. TP53 was analyzed by direct sequencing of its full coding sequence and intron-exon boundaries in 11 fragments. DNA was extracted from paraffin-embedded or frozen specimens. High-resolution genomic copy number profiling was carried out by UCL Genomics on the Affymetrix Human Mapping 250K Nsp or Genome-Wide Human SNP Array 6.0 platform. Both cases demonstrated a strong association between the appearance of anaplastic clones and TP53 mutations. Synchronous ganglioneuroma was diagnosed in one case. Our cases are unique as they represent a long disease history and demonstrate the difficulties in managing rare cases of bilateral WT with anaplasia. These cases also emphasize the practical importance of modern molecular-genetic techniques and their clinical application. Moreover, they highlight the issue of the adequate sampling needed in order to gather comprehensive, efficient, and sufficient information about genetic events in a single tumor.